The Effect of Allowance for Bad Debt Loss to the Level of Profitability - Nurdiansyah Dian Hakip (ECONOMICS, 2018)
Local Bank (BPR) as one of the financial institutions in Indonesia in carrying out its activities collecting funds from the public in the form of savings and deposits and channeling back the funds collected through the provision of credit. This study aims to determine, describe and explain the Effect of Allowance for Bad Debt to the Level of Profitability in Subang BPR of Pabuaran Branch. The method used is descriptive method, and testing of the data - the data studied. The data used is data from the financial statements of PD BPR Subang of Pabuaran Branch in 2012 to 2015 with a monthly ratio reports. Any increase in the value of allowance for bad debt (X) of 1% would cause a rise in the value of profitability level in terms of the comparison of operating cost with operating income (Y) of 0.333% and vice versa. The conclusion is the level of allowance for bad debt does not significantly affect the level of profitability as measured by the comparison of operating expenses to operating income.